How Did the 2008 Economic Crisis Affect Central Banks’ Research Topics? The Case of CEMLA Associates and Collaborating Members - María Luisa Lascurain-Sánchez; Núria Bautista-Puig; Elena López-de-la-Fuente; Elías Sanz-Casado (Revista de Economía Mundial, 2023)
Central banks play a fundamental role in a country’s monetary policy. This study has a twofold objective: a) to analyse the contribution to academic research made by the associates and collaborating members of the Center for Latin American Monetary Studies (CEMLA) and b) to analyse the evolution of research topics in the economic literature over the pre-crisis and crisis periods. Eighteen banks were subjected to bibliometric analysis covering the period 2000-2019. The results show that, although the number of publications is higher for the collaborating members, the growth rate over time is higher in the associates. Associates collaborate less with other institutions in the crisis period than collaborating members. The evolution of topics reveals important differences between the two groups.